2015
DOI: 10.1038/nplants.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

The non-processive rice kinesin-14 OsKCH1 transports actin filaments along microtubules with two distinct velocities

Abstract: Microtubules and actin filaments function coordinately in many cellular processes(1-3). Although much of this coordination is mediated by proteins that statically bridge the two cytoskeletal networks(4-6), kinesin-14 motors with an actin binding calponin homology domain (KCHs) have been discovered as putatively dynamic crosslinkers in plants(7,8). OsKCH1, a KCH from rice, interacts with both microtubules and actin filaments in vivo and in vitro(9). However, it has remained unclear whether this interaction is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…Although some occasional brighter and presumably aggregated particles moved processively towards the microtubule minus ends (white arrow, Fig. 3d and Supplementary Movie 8), individual GFP-KlpA-Δtail molecules behaved like other nonprocessive kinesin-14s (refs 31, 36, 42) and mostly interacted with the microtubules in a diffusive manner with no apparent directional preference (yellow arrow, Fig. 3d and Supplementary Movie 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some occasional brighter and presumably aggregated particles moved processively towards the microtubule minus ends (white arrow, Fig. 3d and Supplementary Movie 8), individual GFP-KlpA-Δtail molecules behaved like other nonprocessive kinesin-14s (refs 31, 36, 42) and mostly interacted with the microtubules in a diffusive manner with no apparent directional preference (yellow arrow, Fig. 3d and Supplementary Movie 8).…”
Section: Resultsmentioning
confidence: 99%
“…Kinesin-14 has been an intriguing kinesin subfamily since the discovery of its founding member Ncd4445 because all kinesin-14s studied to date are exclusively minus end-directed based on the microtubule-gliding experiments313542444546474849. In addition, no kinesin-14 has been shown to be able to generate processive motility on the microtubule as a single homodimer.…”
Section: Discussionmentioning
confidence: 99%
“…We currently favor this idea because it has recently been shown that the dimeric rice Kinesin-14 OsKHC1, which cross-links actin filaments and microtubules, is subject to such an effect. OsKHC1 moves at different velocities on the microtubule depending on the relative orientation of the polar actin filaments to which it is attached (23). It remains unclear why such torsion would affect one pair of motor domains in a Kif15 tetramer over the others.…”
Section: Discussionmentioning
confidence: 99%
“…Tansley insight New Phytologist defects in division-plane orientation (Mineyuki & Palevitz, 1990;McDowell et al, 1996;Sano et al, 2005;Rasmussen et al, 2011a;Va skebov a et al, 2017). PPB actin-microtubule interactions are possibly mediated by actin and microtubule-binding proteins that localize to the PPB, such as formins (Li et al, 2010), Myosin VIII (Wu & Bezanilla, 2014), or kinesins (Buschmann et al, 2011;Klotz & Nick, 2012;Schneider & Persson, 2015;Tian et al, 2015;Walter et al, 2015;Tseng et al, 2017;Yamada et al, 2017). The potential role of microtubule-actin crosslinking proteins in refining division-plane orientation or PPB narrowing is still unknown.…”
Section: Reviewmentioning
confidence: 99%